Behavioural Characteristics of Children with Developmental Disorder Risks - Lavrova, M; Suleymanova, E; Lvova, O; Solominova, A (KnE Life Sciences, 2018)
The article is devoted to the study of the temperament and behaviour of children with developmental disorder risks. Early age is most significant in terms of early identifying deviant development markers for implementing effective programmes for early intervention. The article deals with the peculiarities of using the Infant Behaviour Questionnaire - Revised (IBQ-R) and its application in scientific research; the results of domestic and foreign research into temperament as a marker/predictor of deviant behaviour are presented. The paper describes the results of a pilot study of differences in behaviour in a sample of 49 children aged 5.6 months. The research involved two groups of test children, a reference group (typically developing children) and the children of developmental risk groups (which included prematurity, family risk of autism spectrum disorders (ASD)/attention deficit and hyperactivity disorder (ADHD), paediatric arterial ischemic stroke). The significant impact of developmental disorder risks on the Perceptual Sensitivity Scale (IBQ-R) as well as the effect of sex and risks on the Approach, Vocal Reactivity (IBQ-R) scale were discovered. There are suggestions that prematurity may have a negative impact on the development of temperament in children aged 6 months. However, in comparison with such factors as the genetic predisposition to atypical development or local brain damage due to paediatric arterial ischemic stroke, prematurity (excluding extremely premature) probably has less influence on the development of temperament and behavioural characteristics. There is a significant heterotypic continuity of individual differences in temperament indicators at an early age, which highlights the need for further research into the issue and the formation of large cohorts of children. Keywords: deviant development markers, behaviour, IBQ-R questionnaire.